The EU Public Diplomacy in the United States under the D. Trump Administration: Challenges, Key Projects and Outcomes - A. N. Marchukov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Public diplomacy is one of the key foreign policy instruments of the European Union for strengthening its international stance. In that regard, Brussels pays special attention to ensuring trust-based relations with the United States, which traditionally acts as the EU’s leading trade and military partner. The apparent cooling in transatlantic relations provoked by harmful rhetoric and practices of D. Trump administration forced the EU to focus on non-traditional channels of interacting with the American audience. In this context, the analysis of the EU’s attempts to adapt its public diplomacy programmes in the United States to the new realities is of particular interest. The first section outlines the political, economic, administrative, and image risks faced by EU diplomats in this area during the presidency of D. Trump (2017−2020). The second section examines the main thematic priorities, mechanisms and projects of the EU public diplomacy aimed at the American audience. The author argues that during the period under review the EU placed special emphasis on advocacy, cultural diplomacy, and exchange programmes for young people. The author concludes that, although European diplomats failed to achieve a qualitative improvement in transatlantic relations during D. Trump’s tenure, the EU public diplomacy demonstrated resilience and flexibility in the face of adverse circumstances. Indeed, the EU diplomats proved their creativity in developing innovative programmes which can be instrumental for future development of the EU public diplomacy in general.